Analisis Kualitas Sabun Cair Dengan Bahan Pengikat Dari Filter Puntung Rokok - Purba, Ira Sylvia; Arnata, I Wayan; Antara, Nyoman Semadi (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Waste is an issue of considerable concern in Indonesia. One form of hazardous waste that is difficult to degrade by the environment is cigarette butt filters. Therefore, there is a need for further handling to provide added value to cigarette butt filters by utilizing them as a binder in soap making. This study aims to analyze the quality of soap with binders from cigarette butt filters and determine the weight of liquid soap and soaking time that produces the best soap. This study used two factors: liquid soap weight (35, 40, and 45 g) and soaking time (10, 20, and 30 minutes). The results showed that soaking time and its interaction had a significant effect on foam stability, while the weight of liquid soap did not show a significant effect. In addition, the weight of liquid soap significantly effected moisture content and density, but not pH and antibacterial ability. The effectiveness index shows that the best treatment to produce soap is the ratio of liquid soap weight of 45 g and soaking time of 10 minutes. The overall acceptance test (hedonic) showed that panelists preferred the soap with the ratio W2B2 (40 g liquid soap, 20 minutes soaking), which had a value of 51 ± 133.